2014
DOI: 10.18388/abp.2014_1899
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific lymphocyte proliferation as a marker of immune response in guinea pigs with sustained Helicobacter pylori infection.

Abstract: Helicobacter pylori (H. pylori) bacteria are human pathogens causing symptomatic gastritis, peptic ulcer or gastric cancer. Little is known about the kinetics of immune responses in H. pylori infected patients because the initial moment of infection has not been identified. Various animal models are used to investigate the immune processes related to H. pylori infection. In this study we checked whether H. pylori infection in guinea pigs, mimicking natural H. pylori infection in humans, resulted in the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…The antigen concentrations were adjusted experimentally or adopted from previously performed experiments[44,47,48,68]. …”
Section: Methodsmentioning
confidence: 99%
“…The antigen concentrations were adjusted experimentally or adopted from previously performed experiments[44,47,48,68]. …”
Section: Methodsmentioning
confidence: 99%
“…Guinea pigs are a convenient model for studying the development of specific adaptive immune response to H. pylori antigens. In our previous study we showed that lymphocytes isolated from mesenteric lymph nodes, particularly CD4 + , but not lymphocytes obtained from peripheral blood responded by proliferation to H. pylori antigens included in GE (Miszczyk et al, 2014). D'elios et al, showed that in humans with H. pylori related chronic gastritis or MALT lymphoma, CD4 + T-cell clones, but not CD8 + , proliferated to H. pylori antigens (D'elios et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…Other than in the spleen may also be a location of sensitized lymphocytes capable of clonal expansion in response to H. pylori antigens. Previously it was shown that lymphocytes of guinea pigs infected with H. pylori, which proliferated in the milieu of GE antigens were deposited in the mesenteric lymph nodes (Miszczyk et al, 2014). Another study showed that antigen-specific lymphocytes from the patients infected with H. pylori were accumulated in the basal membrane of the gastric mucosa (Quiding-Jarbrink et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations